Analisis Pengaruh Zakat terhadap Peningkatan Kesejahteraan Mustahiq - Ali Hardana; Desy Khairani; Putri Bunga Daulay; Rizky Pratiwi (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2022)
South Tapanuli Regency BAZNAS distributes zakat to mustahiq without seeing fur, race, and ethnicity among the people in the South Tapanuli region. From various types of zakat distribution by BAZNAS, each program must pay attention to two main components, namely goals and strategies. Puprose: This study aims to determine the increase in zakat on improving the welfare of mustahiq in South Tapanuli Regency BAZNAS. Methodology: This research is a quantitative study using a simple regression analysis method, and data collection instruments using questionnaires and documentation. With a sample of 144 mustahiq. Results: Showed that zakat increases towards increasing mustahiq. Based on the coefficient of determination test, zakat can increase the welfare of mustahiq by 63.5% while the remaining 36.5% requires other factors.